Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.5430/ijfr.v11n2p281
|View full text |Cite
|
Sign up to set email alerts
|

The Manufacture and Service Companies Differ Leverage Impact to Financial Performance

Abstract: The purpose of this research is to examine the leverage from firm. The firms use leverage to expand their source of fund by using external fund such as debt. By usingdebt, financial performance of the firm will develop. Beside the leverage, the use of size and inflation are also considered to be the factors that influence the financial performance while the firms are using leverage. As an independent variable, size is reflected by the assets and the leverage or debt by using the debt ratio to the total of asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
(31 reference statements)
0
6
0
1
Order By: Relevance
“…This condition can make investors afraid to invest their money in the company. The use of debt will determine the level of the company's financial leverage because if it uses more debt than its own capital, the fixed burden to be borne by the company becomes high and this condition can make the company's performance to decline (Yoon and Jang, 2005;Shaferi et al, 2020). H 2 : Company leverage has negative impact on the company financial performance.…”
Section: Levels and Financial Performancementioning
confidence: 99%
See 1 more Smart Citation
“…This condition can make investors afraid to invest their money in the company. The use of debt will determine the level of the company's financial leverage because if it uses more debt than its own capital, the fixed burden to be borne by the company becomes high and this condition can make the company's performance to decline (Yoon and Jang, 2005;Shaferi et al, 2020). H 2 : Company leverage has negative impact on the company financial performance.…”
Section: Levels and Financial Performancementioning
confidence: 99%
“…Tsoutsoura (2010) and Ali (2020) found that leverage is negatively related to financial performance because greater debt has the potential to increase the risk of the company so that investors are hesitant to invest in the company. The use of debt will determine the level of financial leverage of the company because if there is more debt than own capital, the fixed burden borne by the company will be high, which can reduce the financial performance (Shaferi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Another study [49] examined the leverage of companies in manufacturing and services. The authors measure the impacts of debt, company size and inflation on financial performance.…”
Section: Firm Size and Corporate Financial Performancementioning
confidence: 99%
“…Perbedaan ini didasari oleh kondisi keuangan Perusahaan dan pola pengambilan keputusan tiap manajer dalam pemilihan dana Perusahaannya (Bas et al, 2009;Kayo et al, 2018). Penggunaan leverage seringkali digunakan pada Perusahaan Manufaktur yang memiliki bermacam-macam Industri (Amedi & Mustafa, 2020;Shaferi et al, 2020) sehingga penggunaan struktur modal menjadi lebih kompleks (Gobenvy, 2014), ditambah lagi dengan persaingan pada dunia bisnis yang semakin tajam yang mengharuskan Perusahaan untuk terus mempertimbangkan faktor-faktor persaingan pasar yang terus berkembang (Boubaker et al, 2017).…”
Section: Latar Belakangunclassified